ChemInform Abstract: Synthesis and Luminescence Properties of NaLa(MoO4)2‐xAGx:Eu3+ (AG: SO42‐, BO33‐) Red Phosphors for White Light Emitting Diodes. Issue 23 (June 2015) - Zhang, Wentao; Li, Junfeng; Wang, Yulong; Long, Jianping; Qiu, Kehui
Abstract The title phosphors are prepared by solid state reactions of (NH4)6Mo7O24, Na2CO3, La2O3, Eu2O3, and (NH4)2SO4 or (NH4)3BO3 (alumina crucibles, 1100 °C, 3 h).